Disaster, reconstruction, and data for social good: the case of wildfires in Portugal. Issue 4 (29th August 2019) - Freitas, Francisco; Mendes, José Manuel
Abstract : Purpose: This study aims to discuss the role of data in a disaster and important reconstruction process currently undergoing in Portugal. Design/methodology/approach: The consequences resulting from the wildfires of 2017 and 2018 are the scope of this research paper. The main goal is to understand the role of data, namely, in terms of identifying existing usage, the derived problems and possible improvements. The given topic will be researched targeting secondary sources. The sources include official reports, legal proceedings and relevant newspaper articles. Findings: In the course of the work, it was possible to identify some important data related pitfalls. Different levels are considered: information prior to extreme events; access to information during the wildfire events; and the problems observed in the aftermath, when tackling reconstruction processes. Civil protection policies in Portugal are failing to integrate population in their socio-technical arrangements. Research limitations/implications: Important implications can derive by the ongoing investigations and trials enduring in Portuguese justice. This is a process receiving strong media coverage, enacting major revisions to the legal framework and to public policies. Social implications: Positive social implications may be derived from a stronger focus on transparency and accountability by public authorities. To achieve that data/information must be perceived in a completely different way, aiming at the public good. For the state, data ownership should not constitute the primary goal. Lack of data and transparency has been undermining social relations in the affected areas. Originality/value: The literature on forest fires is vast, although there are little concerns on the role of data to improve policymaking and to produce positive social impacts, especially in the aftermath of catastrophes. The Portuguese example underlines how information sharing and transparency are important to safeguard social bonds.